Neutrophils against pathogens of invasive mycoses: Conventional and nontraditional fighting tools - E. A. Mezentseva; I. I. Dolgushin (Медицинская иммунология)
The aim of the present review is to analyze the behavioral strategies and mechanisms of antifungal activity of neutrophils against Candida and Aspergillus based on data published in open scientific sources. Invasive mycoses are systemic diseases caused by microscopic fungi, characterized by high morbidity and mortality in immunocompromised individuals, especially those with neutropeniA. Neutrophils have significant antifungal activity against Candida spp. and Aspergillus spp. C. albicans, the most common causative agent of invasive candidiasis, exhibits a pronounced morphological plasticity. When neutrophils are unable to phagocytize fungal hyphae, they choose another defense mechanism, forming NETs as a result of NETosis. The C. albicans biofilms cause active migration and adhesion of neutrophils, but, unlike planktonic forms, they suppress the release of NETs thus promoting survival of the pathogen. Clusters of C. albicans yeasts and A. fumigatus conidia induce neutrophil swarming, an LTB4-mediated, coordinated, and tightly controlled process characterized by accumulation of neutrophils at the site of infection and aimed at its isolation from healthy tissues. Intravascular neutrophil swarming occurs in the lungs during candidemia, which is a specific defense response to fungal pathogens. In systemic candidiasis, a subpopulation of neutrophils is transformed to PMN-DCs, which demonstrate effective killing and induce an antigen-specific immune response against fungal pathogens. A. fumigatus conidia induce human neutrophils to release extracellular vesicles with potential fungicidal activity. Spores of fast-growing A. fumigatus strains stimulate an influx of neutrophils, facilitating rapid clearance of the fungal pathogen; conidia of slower-growing strains are capable of long-term persistence due to lower neutrophil attraction and survival inside macrophages. Interaction of neutrophils with growing A. fumigatus hyphae results in swarming, NETosis, and ROS generation; the degree of hyphal branching affects their susceptibility to neutrophil-mediated killing: the most branched hyphae are more vulnerable and die first. A. fumigatus hyphae cause activation of NADPH-oxidase and myeloperoxidase in neutrophils with ROS generation which exert a cytotoxic effect and induce the formation of NETs with a predominantly fungistatic effect. Thus, the available data and further study of the mechanisms of neutrophil antifungal activity may provide the basis for development of new pathogenetic concepts, preventive, therapeutic and diagnostic approaches to the causative agents of invasive mycoses.